Is there a trade-off between job security and wages in Germany and the UK? - Dominik Hübler; Olaf Hübler (Institute for the Study of Labor (IZA), 2006)
This paper looks at the wage effects of perceived and objective insecurity in Germany and the UK using the GSOEP and BHPS panels. The distinction between perceived worry about job loss and economic indicators such as regional unemployment rates and the share of temporary contracts is established. The bargaining hypothesis that job security and wages are complements because of union bargaining power and preference is derived from a variant of the right to manage model. This hypothesis is contrasted with Rosen's theory of equalising differences where security and wages are substitutes. The empirical literature surveyed finds evidence for both sides. When addressing a number of econometric issues in earlier studies of the bargaining hypothesis this paper finds strong evidence in favour of the former. Accounting for simultaneous determination of job insecurity and wages significantly negative level effects are found for Germany with some evidence for those in the UK. There is also some evidence for growth rate effects (especially for perceived insecurity), but it does not appear robust. Job insecurity, both perceived and objective is found to have influenced wage development in both countries.
Keywords: J28; J31; J63; J81; 330; job security; wages; Germany; UK